2002 Annual Conference Proceedings
DOI: 10.18260/1-2--10723
|View full text |Cite
|
Sign up to set email alerts
|

Machine Vision Applications Within A Manufacturing Engineering Technology Program

Abstract: The implementation and usage of industrial automation is undergoing major and rapid changes. This change is driven by the need for industry both remain competitive in their cost structure and to increase the levels of quality and consistency in the products that are produced. Today, companies can implement automation at a reasonable price, through advances in sensor technology, networking capabilities, microprocessor design, open architecture for machine controls, Internet applications in machine control, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The NIU Manufacturing Engineering Technology (MET) program has been in the process of revising its curriculum to reflect needed industry skills 12 . Through feedback from Departmental industrial advisory boards, several areas were identified for improvement or incorporation into the curriculum.…”
Section: Technology Curriculum Structure At Northern Illinois Universitymentioning
confidence: 99%
“…The NIU Manufacturing Engineering Technology (MET) program has been in the process of revising its curriculum to reflect needed industry skills 12 . Through feedback from Departmental industrial advisory boards, several areas were identified for improvement or incorporation into the curriculum.…”
Section: Technology Curriculum Structure At Northern Illinois Universitymentioning
confidence: 99%
“…The user can alter the serstyle parameter of the jevois::StdModule to format the serial messages being received. The precision of the serial message being sent can be changes by using the serprec parameter of the StdModule with serprec being 0 for integer, 1 for float numbers with one decimal position and 2 for precision up to two decimal points 4 . A walkthrough about programming in JEvois and about the above-mentioned serial communication is provided to the students.…”
Section: Design Of Object Tracking Systemmentioning
confidence: 99%
“…Some typical applications with vision systems are work piece identification, work piece positioning, work piece dimension measurement, position compensation, surface painting, and vision tracking. Therefore, there is a need to introduce vision system technology to the students who are interested in advanced manufacturing engineering and technology [4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…From this board, the results of the vision inspection can be electronically send to another I/O system or used for other control purposes. Details of how this has been incorporated in NIU's Technology program have been presented elsewhere 4 .…”
Section: Figure 1 6-axis Robot and Empty Bottle Loading Rackmentioning
confidence: 99%
“…Through this cell the students are instructed on several areas of automation. A number of cameras already installed independently in the lab 4 are used for experiments on machine vision. The students acquire skills on usage of vision and the integration of vision with other components.…”
Section: Learning Outcomesmentioning
confidence: 99%